Unique Challenges for Florida Growers in Tomato and Pepper Production - G. McAvoy; M. Ozores-Hampton (EDIS)
IPM-201, a 5-page illustrated fact sheet by G. McAvoy and  M. Ozores-Hampton. was originally compiled from material in “Chapter 2 - Tomato and Pepper Production” of the Grower’s IPM Guide for Florida Tomato and Pepper Production. Originally published August 2007, this update October 2017.